Nullifying vs. dummifying players or nullified vs. dummified players: The difference between the equal division value and the equal surplus division value - André Casajus; Frank Hüttner (Universität Leipzig, Wirtschaftswissenschaftliche Fakultät, 2012)
We provide new characterizations of the equal surplus division value and the equal division value as well as of the class of their convex mixtures. This way, the difference between the Shapley value, the equal division value, and the equal surplus division value is pinpointed to one axiom. Moreover, we shed light on solidarity principles embodied in the equal division value and in the equal surplus division values.
Keywords: C71; D60; 330; solidarity; nullifying player; equal division value; equal surplus division value; desirability